Undergraduate student’s perception of online learning in English speaking class - Cut Fatin Nabilla; Endang Komariah; Nur 'Ain Binti Mohd Jani (English Education Journal, 2022)
Student perception offers numerous information about students’ experiences in online courses, provides lecturers with valuable feedback, indicates how much students learn, and shows the quality of the teaching and learning process. The current study is aimed to find out the students’ perception of speaking class conducted online in terms of usefulness, effectiveness, and intentions. The questionnaires employed in this quantitative study were the students’ perceptions of the online speaking course, which were completed by 112 undergraduate EFL students. The descriptive statistics consisted of five number summary were used to analyze the data. The findings showed that the students had different perceptions about online learning for a speaking class. The students’ perceptions of the online speaking class are mostly positive in the terms of usefulness and effectiveness. However, most of the students did not have positive intention to enroll in online speaking class in the future. Therefore, lecturers are suggested to use interactive methods in delivering the learning material with the use of video conferences such as Zoom and Google Meet.